GERT-network synthesis of vulnerability testing technology of web-applications - Коваленко, Олександр Володимирович (Ukrainian Information Security Research Journal, 2018)
The paper presents research results and vulnerability testing algorithms for one of the most common types of attacks on Web applications - DOM XSS and SQL injection. The approach of mathematical modeling based on GERT-networks is argued. A set of mathematical models of Web application testing technology has been developed. The basis of mathematical modeling is the approach of GERT-network synthesis. As a result, mathematical models of DOM XSS testing technology and vulnerability testing technology for SQL injections have been developed. The mathematical model of the DOM XSS testing technology vulnerability differs from the known, taking into account the execution or analysis of the DOM structure. The mathematical model of vulnerability testing technology for SQL injections differs from the known ones by an improved method of determining the distance between the results of injection.